2020
DOI: 10.31002/rep.v5i1.2050
|View full text |Cite
|
Sign up to set email alerts
|

Komparasi Proses Inovasi Dalam Perspektif Kebijakan Pemerintah Daerah dan Daya Saing Daerah

Abstract: Regional competitiveness is an indicator of development that can be pursued by innovation, innovation in the process requires commitment in the form of policy, this is what distinguishes developmental development between regions. The purpose of this study is to analyze the innovation process, policies in the innovation process and evaluate the regional competitiveness of the innovation process that occurs in four regions, Magelang City, Pekanbaru City, Labuhanbatu Regency and Tuban Regency. Descriptive analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 1 publication
0
11
1
3
Order By: Relevance
“…The average weight gain of normal children aged 12-60 months for boys is 0.18 kg/month and for girls is 0.19 kg/month. The mean height increase for boys was 0.67 cm/month and for girls 0.49 cm/month (30). That is, the growth in body weight and height in this study exceeds the growth rate of normal children, both in boys and girls.…”
Section: Effects Of Providing Local Snacks Accompanied By Virtual Nutrition Counseling On Growth Of Stunting Children Under Fivecontrasting
confidence: 53%
“…The average weight gain of normal children aged 12-60 months for boys is 0.18 kg/month and for girls is 0.19 kg/month. The mean height increase for boys was 0.67 cm/month and for girls 0.49 cm/month (30). That is, the growth in body weight and height in this study exceeds the growth rate of normal children, both in boys and girls.…”
Section: Effects Of Providing Local Snacks Accompanied By Virtual Nutrition Counseling On Growth Of Stunting Children Under Fivecontrasting
confidence: 53%
“…The respondents' income description presented in Table 1 showed that most respondents had an income less than the regional standard (63.8%). It raises workers' dissatisfaction with the salary they have been received and makes it insufficient to meet their daily needs [20]. The inadequate salary was associated with the incidence of workplace stress (p = 0.001) [17].…”
Section: Description Of Respondent Characteristicsmentioning
confidence: 99%
“…Depending on the temperature, certain materials in a thermomechanical actuator help control the collector's angle of inclination to face the sun and provide increased production of about 39% compared to a fixed system. In addition, there are some bioenergy applications, where rotary actuators are used for agricultural machinery and the automation of geographically distributed biogas systems; portable wind energy applications [31] with actuator-controlled over-speeding; wave energy applications, where actuators are used in power-generation purposes [32]; smart grid or microgrid environment [33], where actuators control power generation and consumption; and geothermal power plants with electric valve actuators.…”
Section: Introductionmentioning
confidence: 99%